Longitudinal Association between Periodontitis and the Risk of Hypertension - John B. Aremu; Cynthia M. Pérez; Kaumudi J. Joshipura (Hindawi Limited, 2023)
Objectives. Hypertension poses a major public health challenge due to its association with increased risk of heart disease, chronic kidney disease, and death. The objective of this study is to evaluate the longitudinal association between periodontitis and the risk of hypertension. Methods. Using a cohort study design, 540 participants free of diagnosed hypertension/prehypertension in the San Juan Overweight Adults Longitudinal Study and with complete 3-year follow-up data were included. Periodontitis was classified according to the 2012 Centers for Disease Control and Prevention/American Academy of Periodontology definition. Participants were considered to have developed hypertension if they reported physician-diagnosed hypertension over the follow-up period or had average systolic blood pressure (SBP) ≥140 mm Hg or diastolic blood pressure (DBP) ≥90 mm Hg at follow-up. Participants free of diagnosed hypertension or prehypertension and with normal BP at baseline (SBP < 120 mm Hg and DBP < 80 mm Hg) were considered to develop prehypertension if they had SBP between 120 and 139 mm Hg or DBP between 80 and 89 mm Hg at follow-up. An additional (secondary) outcome was defined as the development of prehypertension/hypertension over the follow-up period among participants who had normal BP at baseline. We used Poisson regression, adjusting for age, sex, smoking status, physical activity, alcohol intake, diabetes, waist circumference, and family history of hypertension. Results. One hundred and six (19.6%) participants developed hypertension, and 58 of the 221 with normal BP (26%) developed prehypertension/hypertension. There was no consistent association between periodontitis and the risk of developing hypertension. However, people with severe periodontitis had an increased incidence of prehypertension/hypertension (multivariate incidence rate ratios: 1.47; 95% confidence interval: 1.01, 2.17) than people without periodontitis after adjusting for confounders. Conclusion. There was no association between periodontitis and hypertension in this cohort study. However, severe periodontitis was associated with an increased risk of prehypertension/hypertension.